Bridge over troubled water: managing compatibility and conflict among thought collectives in sustainability science - Soininen, Niko; Raymond, Christopher M.; Tuomisto, Hanna; Ruotsalainen, Laura; Thorén, Henrik; Horcea-Milcu, Andra-Ioana; Stojanovic, Milutin; Lehtinen, Sanna; Mazac, Rachel; Lamuela, Carlos; Korpelainen, Noora; Vainio, Annukka; et al. (Springer, 2022)
Sustainability transformations call forth new forms and systems of knowledge across society. However, few tools and processes exist for promoting dialogue among different interests and normative stances in knowledge co-creation. In this article, we build on the notion of thought collectives to argue that understanding and moderating normative tensions are necessary if sustainability science is to provide successful solutions. Drawing on an analysis of the normative tensions between rival high-tech and low-tech thought collectives in the mobility and food production sectors, we discuss three strategic approaches: applying common evaluative frameworks, building contextual convergence and embracing complexity. We argue that these strategies indicate a need to distinguish different kinds of reflexivity in managing tensions among thought collectives. As a practical conclusion, we establish sets of reflexive questions to help sustainability scientists deploy the knowledge management strategies discussed.
Keywords: Thought collective; Sustainability science; Research management; Refexivity; Mobility; Food production; Thought collective; Sustainability science; Research management; Refexivity; Mobility; Food production